Intense ү-Ray Bursts following the Interaction of Laser Pulse with Steep Density Gradients. (18th June 2022) - Chintalwad, S.; Krishnamurthy, S.; Morris, S.; Ramakrishna, B.
Abstract : We investigate the production of intense ү-rays following the interaction of ultraintense laser pulse with a hybrid combination of under-dense plasma associated with a thin foil of fully ionized Al or Cu or Au at the rear side. Relativistic electrons are accelerated following the interaction of high intensity laser pulses with an under-dense plasma. These electrons are then stopped by the thin foils attached to the rear side of the under-dense plasma. This results in the production of intense-ray bursts. So, the enhancement of photon generation is due to the under-dense plasma electrons interacting with different over-dense plasma. Using open-source PIC code EPOCH, we study the effect of different electron densities in the under-plasma on photon emission. Photon emission enhancement is observed by increasing the target Z in the hybrid structure. Hybrid structure can enhance photon emission; it can increase the photon energy and yield and improve photon beam divergence. Simulations were also performed to find the optimal under-dense plasma density for ү-ray production.